LibsensorPy - A Library to Improve the Development of Ubiquitous Applications on Raspberry Pi - Marques Neto, Manoel Carvalho; Jesus Jr., Edivaldo M. F. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2015: Proceedings of the 21st Brazilian Symposium on Multimedia and the Web, 2015)
Commonly, programmers who have no knowledge in electronics, and engineers, who have no programming experience, are involved in projects that aims to build ubiquitous systems. To create such systems, they often face the problem of not having the specific knowledge to deal with activities like: implement system’s abstractions, configure logic connections between sensors and a computer device, capture, understand and process data from sensors in order to make them understandable, etc. To fill this gap, this paper presents a library named LibsensorPy, an extensible library which allows to abstract much of the complexity of these activities and more easily interact with an environment through sensors and actuators coupled to a Raspberry Pi computer.